2022
DOI: 10.1093/mnras/stac3285
|View full text |Cite
|
Sign up to set email alerts
|

Chandra measurements of gas homogeneity and turbulence at intermediate radii in the Perseus Cluster

Abstract: We present a Chandra study of surface brightness fluctuations in the diffuse intracluster medium of the Perseus Cluster. Our study utilizes deep, archival imaging of the cluster core as well as a new mosaic of 29 short  5 ks observations extending in 8 different directions out to radii of r500 ∼ 2.2 r2500. Under the assumption that the distribution of densities at a given radius is log-normally distributed, two important quantities can be derived from the width of the log-normal density distribution on a given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…In the turbulent re-acceleration model, cosmic rays gain energy from the interaction with the turbulent motions in the ICM. As turbulence is best studied with X-ray observations (e.g., [123][124][125][126][127][128] and references there), it is obvious to study the correlation between the X-ray and radio emissions of radio halos (e.g., [101,117,129,130] and references therein). Especially, a study of the point-to-point correlation between the radio emission and X-ray emission allows us to study the acceleration mechanism and the magnetic field distribution in galaxy clusters [131][132][133].…”
Section: Turbulent Re-accelerationmentioning
confidence: 99%
“…In the turbulent re-acceleration model, cosmic rays gain energy from the interaction with the turbulent motions in the ICM. As turbulence is best studied with X-ray observations (e.g., [123][124][125][126][127][128] and references there), it is obvious to study the correlation between the X-ray and radio emissions of radio halos (e.g., [101,117,129,130] and references therein). Especially, a study of the point-to-point correlation between the radio emission and X-ray emission allows us to study the acceleration mechanism and the magnetic field distribution in galaxy clusters [131][132][133].…”
Section: Turbulent Re-accelerationmentioning
confidence: 99%
“…Since the advent of high-spatial-resolution X-ray imaging spectroscopy with the Chandra and XMM-Newton observatories, it has been possible to study in detail features such as shocks and cold fronts (Markevitch & Vikhlinin 2007), gas sloshing (e.g., Ascasibar & Markevitch 2006;Roediger et al 2011;ZuHone et al 2011;Johnson et al 2012;Simionescu et al 2012;Paterno-Mahler et al 2013), cavities associated with feedback from active galactic nuclei (McNamara et al 2000;Fabian 2012), and the cool, dense cores found in some clusters (Peterson & Fabian 2006). More recently, such data have been used in investigations of turbulence (Churazov et al 2012;Zhuravleva et al 2015Zhuravleva et al , 2016Zhuravleva et al , 2018Zhuravleva et al , 2019Arévalo et al 2016) and gas clumping in cluster outskirts (Eckert et al 2015;Mirakhor & Walker 2021;de Vries et al 2023), the latter having been spearheaded by lower-resolution but also lower-background Suzaku observations of relatively nearby systems (Simionescu et al 2011;Urban et al 2011Urban et al , 2014Walker et al 2012aWalker et al , 2012b.…”
Section: Introductionmentioning
confidence: 99%